Public Perception of Quality and Support for Required Access to Drinking Water in Schools and Parks. Issue 1 (January 2018) - Long, Michael W.; Gortmaker, Steven L.; Patel, Anisha I.; Onufrak, Stephen J.; Wilking, Cara L.; Cradock, Angie L.
Purpose: We assessed public support for required water access in schools and parks and perceived safety and taste of water in these settings to inform efforts to increase access to and consumption of tap water. Design: Cross-sectional survey of the US public collected from August to November 2011. Setting: Random digit-dialed telephone survey. Participants: Participants (n = 1218) aged 17 and older from 1055 US counties in 46 states. Measures: Perceived safety and taste of water in schools and parks as well as support for required access to water in these settings. Analysis: Survey-adjusted perceived safety and taste as well as support for required access were estimated. Results: There was broad support for required access to water throughout the day in schools (96%) and parks (89%). Few participants believed water was unsafe in schools (10%) or parks (18%). Conclusion: This study provides evidence of public support for efforts to increase access to drinking water in schools and parks and documents overall high levels of perceived taste and safety of water provided in these settings.